An empirical investigation of disclosure item of internet financial reporting in Malaysia - Ali Khan, Mohd Noor Azli (2015)
This research attempts to investigate the current status on the disclosure item of internet financial reporting (IFR) among listed companies in Bursa Malaysia based on preparers and users perception. Content analyses are used to provide evidence on internet financial reporting practices by 280 listed companies.The issues of the disclosure item of IFR of the companies listed in Bursa Malaysia.According to a comprehensive review, the evaluation of IFR will be separated into two dimensions which are content dimension and presentation dimension.The items of disclosure in the development of the IFR disclosure index are based on the perspective of preparers and users. Based on the research findings, the level of IFR started from 56.43 to 87.14 per cent.The findings also showed that the overall level of IFR listed companies in Bursa Malaysia were considered good. The implications of the research findings and future research have been discussed.